Violence and crime in nineteenth-century England : the shadow of our refinement - Wood, J. Carter (John Carter), 1970- (Routledge studies in modern British history ;, 2004)
This book illuminates the origins and development of violence as a social issue by examining a critical period in the evolution of attitudes towards violence. It explores the meaning of violence through an accessible mixture of detailed empirical research and a broad survey of cutting-edge historical theory. The author discusses topics such as street fighting, policing, sports, community discipline and domestic violence and shows how the nineteenth century established enduring patterns in views of violence. Violence and Crime in Nineteenth-Century England will be essent.